(untitled) (Research, Society and Development, 2020)
Plethysmography is an exam used to measure variables of the ventilatory pattern, such as the smallest possible variation in the volume of the chest wall, breath to breath and its compartments. A careful assessment of respiratory function in children and adolescents is necessary for the early identification of changes that impact the respiratory system. The aim of this study was to review the use of Plethysmography as a resource for respiratory assessment in children and adolescents. The present study is a systematic review. A bibliographic survey was carried out in the databases Physiotherapy Evidence Database, Public Medline and Latin American and Caribbean Literature in Health Sciences. The descriptors selected for the search for the articles were: Plethysmography, Respiratory function test, Children and Adolescents. Including clinical trials and observational studies. The exclusion criteria involved studies that involved adults and that did not address the theme. Thirteen scientific articles were included that showed Plethysmography as a resource for respiratory assessment in children and adolescents. The selected articles totaled a sample of 829 participants. The age of the selected participants ranged from 3 to 19 years. The main Plethysmographic data evaluated were: tidal volume, expiratory reserve volume, intrathoracic gas volume, residual volume ratio, forced vital capacity, proportion of inspiratory and expiratory flow, respiratory rate and total lung capacity. It is concluded that, in the studies reviewed, Plethysmography proved to be a very safe and effective resource to assess lung volumes in children and adolescents.